Diseño de un Manual de Control Interno para el Área Administrativa, Contable y Tributaria en la Comercializadora COILE S.A Período 2021 - Rivas Hurtado, Isaac Marcelino (2023)
The Curriculum Integration job named DESIGN OF AN INTERNAL CONTROL MANUAL FOR THE ADMINISTRATIVE, ACCOUNTING AND TRIBUTARY AREA IN COMERCIALIZADORA COILE S.A PERIOD 2021, was carried out with the purpose of designing the procedures that are carried out in the administrative section, accounting and tributary, whose purpose is to verify and control that the information obtained by the operation of the company will be effective and reliable. In order to fulfill the objective in the design of the internal control manual of the present curricular integration job, the current situation of the company was determined, through the application of a research technique in order to obtain the necessary information about the operations that are carried out in the company, followed by the design of procedures, policies and flowcharts that will facilitate the compliance with the administrative, accounting and tributary processes that are performed in the company. Related to the application of the research technique with the results obtained a SWOT analysis was elaborated in which the strengths were determined, which opportunities represent the positive aspects of the company, the weaknesses and threats were also pointed out, which give as result in the corrective measures to be implemented in the design of the internal control manual. In the administrative section, a manual of functions was made in which the responsibilities that each employee of the company has is described, in addition the development of procedures for the selection and hiring, training, entry and exit registration, and, permissions, licenses and staff vacations; in terms of accounting, control formats and accounting entries were designed for the processes that are carried out in the company, such as cash settlement, bank reconciliation, petty cash management, inventory control, account control receivable and payable, among others; On the other hand, in tributary matters, the tributary obligations of the company were taken into consideration, indicating the dates of the declaration and its form to present the declarations in the Internal Revenue Service, in addition, flowcharts were designed, with the purpose of explaining in a simple and fast way each step to follow in the administrative, accounting and tributary procedures carried out by the company; therefore it was possible to determine that the lack of an internal control manual does not allow the activities to be carried out efficiently in the company and the breach of the obligations of the staff in carrying out their daily tasks is generated, for which it is suggested to take as a reference the present internal control manual whose purpose is to improve the processes that are carried out in the company, in order to verify, organize and identify the information that is generated by the operations carried out by the company